Comparing the Aims of University Departments of English with Those of the Department Subjects - Betti, Mohammed Jasim; Lehwag, Jasim Enad (Journal of Ecohumanism, 2024)
The present study seeks to compare the aims of departments of English (henceforth DsE) at the university level in Iraq with the subjects of these departments, and stating whether those subjects contribute to achieve the aims of DsE which are found in four colleges respectively: Colleges of Education for Humanities (henceforth CsEHs), Colleges of Basic Education (henceforth CsBE), Colleges of Languages (henceforth CsLs) and Colleges of Arts (henceforth CsAs). The study aims at: (1) Listing the colleges that teach English as a foreign language (EFL) in Iraq.(2) Listing the subjects of the DsE in the cited above colleges. (3) Analyzing the subjects of the stages of the DsE to see if they achieve the aims of the DsE in Iraqi CsEHs, CsBE, CsLs and CsAs. This study hypothesizes that the subjects of the DsE in Iraq achieve the aims of departments. This study concludes that (1) The investigation of the subjects of DsE proved that these subjects achieve the aims of these departments. (2) The DsE subjects differ from on college to another. (3) It is necessary to reformulate the aims of DsE in order to coincide the vast scope of aims of subjects that are taught in different colleges